Mechanisms of Fibrinogen Adsorption at Solid Substrates - Adamczyk, Zbigniew; Bratek-Skicki, Anna; Zeliszewska, Paulina; Wasilewska, Monika (Current Topics in Medicinal Chemistry, 2014)
The aim of this work was to critically review recent results pertinent to fibrinogen adsorption at solid/electrolyte interfaces with the emphasis focused on a quantitative analysis of these processes in terms of the electrostatic interactions. Accordingly, in the first part, the primary chemical structure of fibrinogen is analyzed. Physicochemical data pertinent to the bulk properties derived from hydrodynamic, dynamic light scattering and micro-electrophoretic measurements aided by theoretical modeling are discussed. Possible conformations and the effective charge distribution over the fibrinogen molecule for various pH an ionic strength are defined, especially the semi-collapsed conformation prevailing at physiological conditions. Adsorption kinetics of fibrinogen at hydrophilic and hydrophobic (polymer modified) substrates determined by various techniques is described. Adsorption at polymeric carrier particles, pertinent to immunological assays, studied in terms of electrokinetic and concentration depletion methods, are also considered. The reversibility of adsorption, fibrinogen molecule orientations and maximum coverages are thoroughly discussed. The stability of fibrinogen monolayers formed at these carrier particles in respect to pH and ionic strength cyclic changes is also discussed. In the final section interactions and deposition of model colloid particles on fibrinogen monolayers are analyzed which allows one to derive valuable information about molecule orientations. Based on the physicochemical data, adsorption kinetics and colloid particle deposition measurements, probable adsorption mechanisms of fibrinogen on solid/electrolyte interfaces are defined.
Keywords: fibrinogen molecule shape and size